Developing Sociodrama-Based Islamic Education and Character Education Learning Module for Junior High School Students - Yacob, Fakhri; Mardhatillah, Liza Safira (DAYAH: Journal of Islamic Education, 2025)
This study was motivated by the limited emotional and social engagement of students in Islamic Education and Character Education (PAI-BP) learning, which often results in learning experiences that are less active, communicative, and meaningful. This study aimed to develop a sociodrama-based PAI-BP learning module for Grade VIII junior secondary school students in Banda Aceh. The sociodrama approach was selected because it allows students to engage with religious and moral values through structured role-playing, social interaction, reflection, and contextual learning activities. The novelty of this study lies in the systematic development of a sociodrama-based PAI-BP module that is contextualized within the Islamic educational environment of Banda Aceh and designed to support active learning and character-oriented instruction. This study employed a Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The development process involved expert validation, practitioner-based practicality testing, and effectiveness testing. The research instruments consisted of expert validation sheets, practitioner response questionnaires, and learning outcome tests administered through pretests and posttests. The data were analyzed using percentage scores to assess validity and practicality, and the N-Gain formula to measure effectiveness. The results show that the sociodrama-based learning module has very high quality. The validity score increased from 89.68% in the first validation stage to 94.51% in the second validation stage, both categorized as highly valid. The practicality test obtained a score of 96.25%, categorized as highly practical, while the effectiveness test showed an N-Gain score of 0.83, categorized as high. These findings indicate that the module is valid, practical, and effective in improving students’ learning outcomes. In addition, its structured sociodrama activities have pedagogical potential to support students’ social interaction, interpersonal communication, empathy, and internalization of religious moral values. Therefore, the module is feasible for use as an innovative instructional material in PAI-BP learning at the junior secondary school level.